2018
DOI: 10.18632/oncotarget.25985
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of Aurora A kinase in Philadelphia chromosome-positive ABL tyrosine kinase inhibitor-resistant cells

Abstract: Abelson murine leukemia viral oncogene homolog (ABL) tyrosine kinase inhibitors (TKIs) have been shown to be effective for treatment of chronic myeloid leukemia (CML) and Philadelphia chromosome-positive (Ph+) acute lymphoblastic leukemia patients. However, resistance to ABL TKIs can develop as a result of breakpoint cluster region-ABL point mutations. Aurora kinases regulate many processes associated with mitosis. In this study, we investigated whether inhibiting Aurora kinase can reduce the viability of Ph+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This hypothesis is supported by the observation that inhibition of ROCK or LIMK hyper-stabilizes mitotic spindles and impairs Aurora kinase A activation, suggesting the implication of the ROCK-LIMK-cofilin axis in Aurora kinase A activation via actin dynamics [16]. It was recently shown that Aurora kinase A is constitutively activated in BCR::ABL+ cells [22]. Furthermore, knockdown of Aurora kinase A enhanced activity of BCR::ABL-targeting TKIs, including leukemic cells harboring BCR::ABL mutations that conferred resistance to TKIs.…”
Section: Discussionmentioning
confidence: 81%
“…This hypothesis is supported by the observation that inhibition of ROCK or LIMK hyper-stabilizes mitotic spindles and impairs Aurora kinase A activation, suggesting the implication of the ROCK-LIMK-cofilin axis in Aurora kinase A activation via actin dynamics [16]. It was recently shown that Aurora kinase A is constitutively activated in BCR::ABL+ cells [22]. Furthermore, knockdown of Aurora kinase A enhanced activity of BCR::ABL-targeting TKIs, including leukemic cells harboring BCR::ABL mutations that conferred resistance to TKIs.…”
Section: Discussionmentioning
confidence: 81%
“…Tyrosine-protein phosphatase non-receptor type 11 (SHP2) plays an important role in CML since it is required to initiate and maintain BCR-ABL-mediated transformation, which is vital in leukemogenesis and hematopoiesis [ 27 ]). Auro-rakinase and mortalin are overexpressed in chronic myeloid leukemia, making them targets for inhibition, especially when conventional TKI inhibitors fail [ 28 , 29 ]). Vascular endothelial growth factor receptor (VEGFR)) and EGFR (vascular endothelial growth factor receptor epidermal) play key roles in leukemia cell proliferation and survival [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Now, Alisertib (MLN8237), AT9283, and Danusertib (PHA-739358) show better results against CML and ALL patients that possess T3151 mutation. This may cause their use as off target agents in addition to other FDAapproved drugs [29].…”
Section: Bcr-abl As a Target For Therapymentioning
confidence: 99%